2000
DOI: 10.1038/sj.leu.2401910
|View full text |Cite
|
Sign up to set email alerts
|

De novo acute B cell leukemia/lymphoma with t(14;18)

Abstract: The t(14;18)(q32;q21) translocation is the most common translocation in B cell malignancies being found in 80% of follicular lymphomas and about 20% of diffuse large B cell lymphomas. Only rare cases of de novo acute B cell lymphoblastic leukemia with t(14;18) have been described. We describe five cases of this entity which appears to have very homogeneous clinical, phenotypic and genotypic features. None of these patients had prior history of follicular lymphoma. The disease was characterized by acute clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 25 publications
(44 reference statements)
2
26
0
Order By: Relevance
“…16,[19][20][21][22][23][24] The molecular structure of the t(8;14;18) rearrangement has been studied in detail in the cell lines DOHH2, VAL and ROS-50. 5 These studies have demonstrated that concurrent deregulation of BCL2 and MYC was achieved by translocation with a single IGH allele, whereby separation of the 3 0 and 5 0 IGH enhancer elements occurs with relocation of the BCL2-5 0 IGH enhancer fusion to the der (8), and translocation of MYC adjacent to the 3 0 IGH enhancer element that is retained on the der (14).…”
Section: Discussionmentioning
confidence: 99%
“…16,[19][20][21][22][23][24] The molecular structure of the t(8;14;18) rearrangement has been studied in detail in the cell lines DOHH2, VAL and ROS-50. 5 These studies have demonstrated that concurrent deregulation of BCL2 and MYC was achieved by translocation with a single IGH allele, whereby separation of the 3 0 and 5 0 IGH enhancer elements occurs with relocation of the BCL2-5 0 IGH enhancer fusion to the der (8), and translocation of MYC adjacent to the 3 0 IGH enhancer element that is retained on the der (14).…”
Section: Discussionmentioning
confidence: 99%
“…4 High expression of Bcl-2, an anti-apoptotic protein, can be associated with drug resistance in hematological malignancies. 4,11,[36][37][38][39][40][41][42][43][44][45][46][47] Thus, even the lower expression of Bcl-2 in some samples could provide an optimal anti-apoptotic effect. The role of Bcl-2 as a prognostic indicator remains controversial and it has therefore been suggested that Bcl-2 should be evaluated in parallel with other apoptotic markers.…”
Section: Leukemiamentioning
confidence: 99%
“…81 The importance of the Bcl-2 family of proteins is underscored by reports of their dysregulation in many hematological malignancies that can contribute to the resistance of such malignancies to pro-apoptotic chemotherapeutic drugs. [82][83][84][85][86][87][88][89][90] Apoptosis due to the cell receiving an abnormal proliferative signal…”
Section: The Bcl-2 Family Of Proteins: the Finger On The Buttonmentioning
confidence: 99%